Effect of Thai traditional antinausea remedy on hypnotic and sedative activity in animal experimental models: Interaction with drugs acting at GABAA receptor - Watchara Damjuti; Juthaporn Kwansang; Jurairat Boonruab (Wolters Kluwer Medknow Publications, 2019)
Thai traditional antinausea remedy is drug registered in the National List of Essential Medicines for the treatment of blood circulation disorders, dizziness, fatigue, and insomnia. Antinausea remedies have long been used, but their effects and action mechanisms remain poorly understood. Here, hypnotic, sedative, and anxiolytic activities of antinausea remedies were evaluated. This preclinical trial assessed the hypnotic, sedative, and anxiolytic activities of antinausea remedies. Thai traditional antinausea remedy was extracted by decoction in deionized water until exhaustion and concentrated to dryness. Anxiolytic activities were evaluated using elevated plus-maze and open-field tests for vehicle control group compared to treatment groups (50, 100, and 200 mg/kg). Hypnotic and mechanistic studies were performed using thiopental sodium-induced sleeping time with benzodiazepine receptor antagonist test. In the thiopental sodium-induced sleeping time test, vehicle control groups were compared to treatment groups (10, 50, and 100 mg/kg). In addition, GABAergic agonistic effect vehicle control groups were pretreated with 3.5-mg/kg flumazenil before sterile water and compared to the treatment group which also received flumazenil before 100 mg/kg extract. Data were statistically analyzed using analysis of variance followed by multiple comparison testing. The aqueous extract was found to be a hypnotic and sedative agent with a dose response either as latent period or prolonged sleeping time (P < 0.05) and a successive GABAergic agonistic effect. Locomotor determination revealed the tendency to relieve anxiety. Thai traditional antinausea remedy can induce sleep and be safely used to reduce anxiety.